The influence of large amplitude planetary waves on the Antarctic ozone hole of austral spring 2017 - Evtushevsky, O; Andrew Klekociuk; Kravchenko, V; Milinevsky, G; Grytsai, A (2020)
Quasi-stationary planetary wave activity in the lower Antarctic stratosphere in the late austral winter was an important contributor to the preconditioning of the ozone hole in spring 2017. Observations show that the ozone hole area in spring 2017 was at the level of 1980s, i.e. almost half the maximum size in 2000s. The observed ozone hole area was close to that forecasted based on a least-squares linear regression between wave amplitude in August and ozone hole area in September–November. We show that the key factor which contributed to the preconditioning of the Antarctic stratosphere for a relatively small ozone hole in the spring of 2017 was the development of large-amplitude stratospheric planetary waves of zonal wavenumbers 1 and 2 in late winter. The waves likely originated from tropospheric wave trains, and promoted the development of strong mid-latitude anticyclones in the lower stratosphere which interacted with the stratospheric polar vortex and strongly eroded the vortex in August and September, mitigating the overall level of ozone loss.